Cytomembrane nanovaccines show therapeutic effects by mimicking tumor cells and antigen presenting cells - Wen-Long Liu (Nature Portfolio, 2019)
Cancer vaccines often fail to generate clinically relevant effects. Here, the authors generate a nanosized cytomembrane vaccine based on fusion between dendritic cells and cancer cells, and show them to activate anti-tumor immune responses via their antigen presenting and T-cell activating functions.